EDUCATIONAL SERIES ON THE SPECIALIST VALVE CLINIC: How to run a specialist valve clinic: the history, examination and exercise test - Chambers, John B (Echo Res Pract, 2019)
Echocardiography is the key to the detection and initial assessment of valve disease. The examination helps differentiate severe from moderate disease if this is unclear from the echocardiogram, but is less useful than echocardiography for surveillance. However, the history is extremely important because symptoms are an indication for surgery in all types of valve disease. In aortic stenosis, the mortality rises soon after the onset of exertional breathlessness or chest tightness. Exercise testing is an extension of the history and may reveal symptoms in apparently asymptomatic patients. This article discusses the history, examination and exercise testing in patients either newly referred or under routine follow-up in a specialist valve clinic.